The law of cyclic evolution of the world, the reality and beingness according to the sign-images on the Malta plate, made from mammoth ivory in the times of Paleolithic Age - Omelchenko V.V. (Вестник археологии, антропологии и этнографии, 2016)
The article examines some sign-images such as a pin-point spiral of the Malta Plate using a system analysis approach. This Plate is the unique archeological artifact and was made of mammoth ivory in the times of the Paleolithic age, in an ancient human location found in Southern Siberia, the village of Malta. These sign-images which are associated with Tripartite knowledge from the Veda and the Avesta, show a well-throughout classification system of upstream and downstream spirals, describing different systems of counting, numeration and calculation. A strict logical correlation between the universal stages of acts of the nature and the spiral turns on the Malta Plate was revealed. It is concluded that this unique archeological artifact reflects the universal global law of cyclic or periodic evolution of objects, processes and events in the world, reality and beingness.